Diversity and host specificity of the Verminephrobacter –earthworm symbiosis - Marie B. Lund; Seana K. Davidson; Martin Holmstrup; Sam James; Kasper U. Kjeldsen; David A. Stahl; Andreas Schramm (Environmental Microbiology, 2010)
Summary Symbiotic bacteria of the genus Verminephrobacter ( Betaproteobacteria ) were detected in the nephridia of 19 out of 23 investigated earthworm species ( Oligochaeta : Lumbricidae ) by 16S rRNA gene sequence analysis and fluorescence in situ hybridization (FISH). While all four Lumbricus species and three out of five Aporrectodea species were densely colonized by a mono‐species culture of Verminephrobacter , other earthworm species contained mixed bacterial populations with varying proportions of Verminephrobacter ; four species did not contain Verminephrobacter at all. The Verminephrobacter symbionts could be grouped into earthworm species‐specific sequence clusters based on their 16S rRNA and RNA polymerase subunit B ( rpoB ) genes. Closely related host species harboured more closely related symbionts than did distantly related hosts. Co‐diversification of the symbiotic partners could not be demonstrated unambiguously due to the poor resolution of the host phylogeny [based on histone H3 and cytochrome c oxidase subunit I (COI) gene sequence analyses]. However, there was a pattern of symbiont diversification within four groups of closely related hosts. The mean rate of symbiont 16S rRNA gene evolution was determined using a relaxed clock model, and the rate was calibrated with paleogeographical estimates of the time of origin of Lumbricid earthworms. The calibrated rates of symbiont 16S rRNA gene evolution are 0.012–0.026 substitutions per site per 50 million years and thus similar to rates reported from other symbiotic bacteria.